Pengaruh Sentra Bahan Alam Terhadap Kemampuan Sains Anak Pada Kelompok B Ra Roudlotul Mujtahidin Jrambe Kecamatan Dlanggu Kabupaten Mojokerto - Ismawati, Putri; Iisnawati, Iisnawati (JCE (Journal of Childhood Education), 2018)
This study aims to improve the ability of children science Group B RA RoudlotulMujtahidin Jrambe Village District Dlanggu Mojokerto through Sentra BahanAlam.Penelitian using quantitative research methods with the type of research isexperimental research. This research uses Pre-Experimental Designs research design usingOne-Group Pre-Test-Post-Test Designs.The value of improvement of the Science Ability of the 26 students who have done theapplication of learning Material Sentra Nature average score or value increased 13.50. TestStatistics above Asymp value. Sig (2-tailed) is 0, Because the value of Asymp. Sig (2-tailed) issmaller than 0.005 then there is a significant effect of the development of childrens ScienceSkills before and after the application of learning Material Sentra Nature. Judging from theanalysis of statistical figures generated through Wilcoxon Test, the result is that theApplication of Learning Center of Natural Resources has an effect on increasing the abilityof children Science in RA Roudlotul Mujtahidin Jrambe. Learning Center Natural Materialsis very effective to improve the development of Science Capabilities of children especially